Place‐based heterogeneity in lung transplant recipient outcomes. Issue 12 (25th August 2022) - Tsuang, Wayne M.; Lopez, Rocio; Tang, Anne; Budev, Marie; Schold, Jesse D.
Abstract : Place is defined as a social or environmental area of residence with meaning to a patient. We hypothesize there is an association between place and the clinical outcomes of lung transplant recipients in the United States. In a retrospective cohort study of transplants between January 1, 2010, and December 31, 2019, in the Scientific Registry of Transplant Recipients, multivariable Cox regression models were used to test the association between place (through social and environmental factors) with readmission, lung rejection, and survival. Among 18, 465 recipients, only 20% resided in the same county as the transplant center. Recipients from the most socially vulnerable counties when compared to the least vulnerable were more likely to have COPD as a native disease, Black or African American race, and travel long distances to reach a transplant center. Higher local life expectancy was associated with lower likelihood for readmission (odds ratio [OR] = 0.90, 95% confidence interval [CI]: 0.84, 0.98, p  = .01). Higher social vulnerability was associated with a higher likelihood of lung rejection (OR = 1.37, [CI]: 1.07, 1.76, p  = .01). There was no association of residence with posttransplant survival. Recipient place‐based factors were associated with complications and processes of care after transplant and warrant further investigation. Abstract : Place, defined as a social or environmental area with meaning to a patient, is associated with lung transplant outcomes, indicating that clinical or transplant center factors alone fail to fully explain outcomes.